Treatment of traumatic irisdefects - Wilczyński, Michał; Owidzka, Marta (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Treating traumatic iris defects is still an important therapeutic problem. Various therapeutic strategies are possible, depending on the etiology of the defect, its size or localization, as well as other coexisting defects of ocular structures. The purpose of this paper was to describe various possible traumatic iris defects, as well as different methods of iris defect repair. In acquired iris defects, ophthalmologists have a relatively wide choice of treatments. Each method is safe and effective; however, it is important to be aware of their limitations. An appropriate choice of treatment strategy for a specific type of iris defect in view of other coexisting ocular defects is crucial.